In vitro inhibition of caprine herpesvirus 1 by acyclovir and mizoribine. (April 2015) - Elia, G.; Camero, M.; Decaro, N.; Lovero, A.; Martella, V.; Tempesta, M.; Buonavoglia, C.; Crescenzo, G.
Highlights: There are biological similarities between CpHV-1 and human herpesvirus type 2. The antiviral effect of Mizoribine and Acyclovir was tested against CpHV-1 in vitro. The combination of Mizoribine and Acyclovir inhibited CpHV-1 replication in vitro. Abstract: Caprine herpesvirus 1 (CpHV-1) infection in goats induces genital vesicular-ulcerative lesions that strictly resemble the lesions induced by herpesvirus 2 in the human host. The immunosuppressive drug Mizoribine (MIZ) was found to increase the antiviral activity of Acyclovir (ACV) against herpesvirus infections, raising interesting perspectives on new combined therapeutic strategies. In this study the anti-CpHV-1 activity in vitro of ACV alone or in combination with MIZ was characterized. When applied alone at non-toxic concentrations, ACV had a slight effect on CpHV-1 replication while in combination with MIZ a dose-dependent inhibition of the virus yield was observed with an IC50 of ACV of 28.5 µM. These findings suggest that combined therapy of ACV and MIZ is potentially exploitable in the treatment of genital infection by herpesviruses.